Analisis Perhitungan Pajak Penghasilan (PPH) 21 Pasca Penerapan UU Harmonisasi Peraturan Perpajakan (HPP) No.7 Tahun 2021 Terhadap Karyawan Penerima Uang Lembur Guna Menentukan Pajak Terutang : (Studi Kasus Di PT. Perkebunan Nusantara X (PERSERO) Pabrik Gula Ngadirejo Kabupaten Kediri) - Jayanti Indah Fresilina; Marhaendra Kusuma; Miladiah Kusumaningarti (Jurnal Mutiara Ilmu Akuntansi, 2023)
The research objective is to analyze the calculation of Article 21 Income Tax after the implementation of the HPP Law no. 7 of 2021 concerning changes to tax rates for employees who receive overtime pay as an additional income and calculating PPh using the Gross method and the Gross Up method. The sampling technique used Total Sampling, namely as many as 50 employees of the Ngadiredjo Sugar Factory who received overtime pay. The results of this study are that changes in tax rates and overtime pay also affect income taxes, such as new regulations causing employee taxes payable to be lower than the old regulations, tax payable per year is Rp.4,451,051.44 for taxes payable per month is Rp. 370,920.95 while in the new regulations in the HPP Law No. 7 for tax payable per year of Rp.3,451,051.44 and for tax payable per month of Rp.287,587.62. In determining the if method, use the Gross Up Method. The payable tax that must be paid by employees is Rp. 278,050.15 per month, whereas if the company uses the Gross Up Method, the tax payable per year is Rp. 13,743,899.44 and Rp. 1,145,324.95 for the monthly tax payable. Based on these data, the Gross Method will be more profitable for companies because the employees themselves will pay the tax owed on their income so that the company will also not bear the tax burden on employees and can save expenses on tax expenses.